The Pygmalion effect : an agency model with reference dependent preferences - Kohei Daido; Hideshi Itoh (Center for Economic Studies and ifo Institute (CESifo), 2005)
We attempt to formulate and explain two types of self-fulfilling prophecy, called the Pygmalion effect (if a supervisor thinks her subordinates will succeed, they are more likely to succeed) and the Galatea effect (if a person thinks he will succeed, he is more likely to succeed). To this purpose, we extend a simple agency model with moral hazard and limited liability by introducing a model of reference dependent preferences (RDP) by K'szegi and Rabin (2004). We show that the agent with high expectations about his performance can be induced to choose high effort with low-powered incentives. We then show that the principal's expectation has an important role as an equilibrium selection device.
Keywords: M12; M54; M52; D82; B49; 330; self-fulfilling prophecy; Pygmalion effect; Galatea effect; reference dependent preferences; agency model; moral hazard; Agency Theory; Leistungsanreiz; Leistungsmotivation; Nutzen; Moral Hazard; Beschränkte Haftung; Theorie